Mechanosensitive regulation of stanniocalcin‐1 by zyxin and actin‐myosin in human mesenchymal stromal cells. (19th May 2020) - Zonderland, Jip; Gomes, David B.; Pallada, Yves; Moldero, Ivan L.; Camarero‐Espinosa, Sandra; Moroni, Lorenzo
Abstract: Stanniocalcin‐1 (STC1) secreted by mesenchymal stromal cells (MSCs) has anti‐inflammatory functions, reduces apoptosis, and aids in angiogenesis, both in vitro and in vivo. However, little is known about the molecular mechanisms of its regulation. Here, we show that STC1 secretion is increased only under specific cell‐stress conditions. We find that this is due to a change in actin stress fibers and actin‐myosin tension. Abolishment of stress fibers by blebbistatin and knockdown of the focal adhesion protein zyxin leads to an increase in STC1 secretion. To also study this connection in 3D, where few focal adhesions and actin stress fibers are present, STC1 expression was analyzed in 3D alginate hydrogels and 3D electrospun scaffolds. Indeed, STC1 secretion was increased in these low cellular tension 3D environments. Together, our data show that STC1 does not directly respond to cell stress, but that it is regulated through mechanotransduction. This research takes a step forward in the fundamental understanding of STC1 regulation and can have implications for cell‐based regenerative medicine, where cell survival, anti‐inflammatory factors, and angiogenesis are critical. Abstract : Secreted stanniocalcin‐1 (STC1) is important for cell survival, but its regulation is largely unknown. We show that STC1 secretion is regulated through the mechanosensitive proteins actin and zyxin. STC1 increased in specific, but not all, cell‐stress conditions and 3D cultures, where actin and zyxin are low. Understanding STC1 regulation is important to optimize transplanted cell survival in regenerative medicine applications.